2016
DOI: 10.15407/ugz2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Natural Atlantic Holocene Stage Conditions Based on the Paleosoil Research of Trypillya Settlement

Abstract: Мета дослідження -реконструювати природні умови часу життєдіяльності трипільського населення на основі палеоґрунтових досліджень поселення біля села Лікареве в Кіровоградській області. Методологічною основою дослідження є використання геоархеологічного підходу, спрямованого на реконструкції природних умов у різні часи життєдіяльності людини на основі синтезу результатів археологічних та палеогеографічних даних. Наукова новизна дослідження полягає в отриманні нових палеоґрунтознавчих даних щодо природних умов в… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The buried soils contained humus horizons 25-30 cm thick, thus being fertile. The groups of later stages of Trypillia from the nearby portions of the Dnieper River basin also exploited chernozem soils (Likareve, Trypillia B2; [44,45,71]). In the site of Sabatynivka 1, the development of chernozem was stopped by erosional event of the late fifth mill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The buried soils contained humus horizons 25-30 cm thick, thus being fertile. The groups of later stages of Trypillia from the nearby portions of the Dnieper River basin also exploited chernozem soils (Likareve, Trypillia B2; [44,45,71]). In the site of Sabatynivka 1, the development of chernozem was stopped by erosional event of the late fifth mill.…”
Section: Discussionmentioning
confidence: 99%
“…Matviishyna and her students at several sites [43]. They revealed that buried soils, when preserved, belonged to several morphological types similar to those existing in the region today [21,22,44,45]. Shorter profiles of the late 5th mill BC soils made them similar to the "chernozems of southern type" developing under open grassland conditions.…”
Section: State Of the Artmentioning
confidence: 98%
“…Палеогеографічна (стратиграфічна) і археологічна періодизація плейстоцену [2] за допомогою технокомплексів обробки кременю, властивих як неандертальцям, так і кроманьйон-цям. Палеопедологічні дані вказують, що природні умови у витачівський час, у місцях життєдіяльності давньої людини, були контрастними, змінно-воло-го-посушливими (помірно-теплі кліматичні умови, темно-бурі, бурі викопні ґрунти, лісостепові ланд-шафти з березово-сосновими лісами, з домішками граба і дуба та злаково-різнотравні степи [6,7]. До бузьких лесів приурочені артефакти гравету, виготовлені кроманьйонцями на стоянках Озерове та Троянове 4.…”
Section: актуальність теми дослідженняunclassified